Question
upstudy study bank question image url

Combine the following expressions. \( \frac{1}{3} \sqrt{45}-\frac{1}{2} \sqrt{12}+\sqrt{20}+\frac{2}{3} \sqrt{27} \) \( 4 \sqrt{5}+\sqrt{3} \) \( 3 \sqrt{5}+\sqrt{3} \) \( 3 \sqrt{3}+\sqrt{5} \)

Ask by Chambers Stuart. in the United States
Feb 28,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The combined expression is \( 11\sqrt{5} + 6\sqrt{3} \).

Solution

To combine the expressions, work step by step. Step 1. Simplify the first expression:  (1/3)√45 – (1/2)√12 + √20 + (2/3)√27 • Simplify (1/3)√45:  √45 = √(9×5) = 3√5 ⟹ (1/3)×3√5 = √5 • Simplify –(1/2)√12:  √12 = √(4×3) = 2√3 ⟹ (1/2)×2√3 = √3 ⟹ –√3 • Simplify √20:  √20 = √(4×5) = 2√5 • Simplify (2/3)√27:  √27 = √(9×3) = 3√3 ⟹ (2/3)×3√3 = 2√3 Now combining these:  √5 – √3 + 2√5 + 2√3 = (√5 + 2√5) + (–√3 + 2√3)  = 3√5 + √3 Step 2. Write down the rest of the expressions as given:  Expression 2: 4√5 + √3  Expression 3: 3√5 + √3  Expression 4: 3√3 + √5  (which can be written as √5 + 3√3) Step 3. Combine all expressions:  Total √5 terms: 3√5 + 4√5 + 3√5 + √5 = (3+4+3+1)√5 = 11√5  Total √3 terms: √3 + √3 + √3 + 3√3 = (1+1+1+3)√3 = 6√3 Final Answer:  11√5 + 6√3

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

Let's simplify and combine the expressions step by step! First, we simplify the square roots: - \( \sqrt{45} = \sqrt{9 \cdot 5} = 3\sqrt{5} \) - \( \sqrt{12} = \sqrt{4 \cdot 3} = 2\sqrt{3} \) - \( \sqrt{20} = \sqrt{4 \cdot 5} = 2\sqrt{5} \) - \( \sqrt{27} = \sqrt{9 \cdot 3} = 3\sqrt{3} \) Now, substituting these back into the original expression: \[ \frac{1}{3}(3\sqrt{5}) - \frac{1}{2}(2\sqrt{3}) + 2\sqrt{5} + \frac{2}{3}(3\sqrt{3}) \] This simplifies to: \[ \sqrt{5} - \sqrt{3} + 2\sqrt{5} + 2\sqrt{3} \] Now, combining like terms: For \( \sqrt{5} \): \[ \sqrt{5} + 2\sqrt{5} = 3\sqrt{5} \] For \( \sqrt{3} \): \[ -\sqrt{3} + 2\sqrt{3} = \sqrt{3} \] Putting it all together, we get: \[ 3\sqrt{5} + \sqrt{3} \] Now let's add the other expressions: Adding \( 4\sqrt{5} + \sqrt{3} \): \[ (3\sqrt{5} + \sqrt{3}) + (4\sqrt{5} + \sqrt{3}) = (3\sqrt{5} + 4\sqrt{5}) + (\sqrt{3} + \sqrt{3}) = 7\sqrt{5} + 2\sqrt{3} \] Adding \( 3\sqrt{5} + \sqrt{3} \): \[ (7\sqrt{5} + 2\sqrt{3}) + (3\sqrt{5} + \sqrt{3}) = (7\sqrt{5} + 3\sqrt{5}) + (2\sqrt{3} + \sqrt{3}) = 10\sqrt{5} + 3\sqrt{3} \] Finally, adding \( 3\sqrt{3} + \sqrt{5} \): \[ (10\sqrt{5} + 3\sqrt{3}) + (3\sqrt{3} + \sqrt{5}) = (10\sqrt{5} + \sqrt{5}) + (3\sqrt{3} + 3\sqrt{3}) = 11\sqrt{5} + 6\sqrt{3} \] Thus, the combined expression is: \[ \boxed{11\sqrt{5} + 6\sqrt{3}} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy